Is enzymatic hydrolysis a reliable analytical strategy to quantify glucuronidated and sulfated polyphenol metabolites in human fluids?. Issue 7 (2nd June 2017) - Quifer-Rada, Paola; Martínez-Huélamo, Miriam; Lamuela-Raventos, Rosa M.
Abstract : Phenolic compound recovery decreases with the amount of β-glucuronidase enzyme used. Abstract : Phenolic compounds are present in human fluids (plasma and urine) mainly as glucuronidated and sulfated metabolites. Up to now, due to the unavailability of standards, enzymatic hydrolysis has been the method of choice in analytical chemistry to quantify these phase II phenolic metabolites. Enzymatic hydrolysis procedures vary in enzyme concentration, pH and temperature; however, there is a lack of knowledge about the stability of polyphenols in their free form during the process. In this study, we evaluated the stability of 7 phenolic acids, 2 flavonoids and 3 prenylflavanoids in urine during enzymatic hydrolysis to assess the suitability of this analytical procedure, using three different concentrations of β-glucuronidase/sulfatase enzymes from Helix pomatia . The results indicate that enzymatic hydrolysis negatively affected the recovery of the precursor and free-form polyphenols present in the sample. Thus, enzymatic hydrolysis does not seem an ideal analytical strategy to quantify glucuronidated and sulfated polyphenol metabolites.